Rancangan Media Informasi Wedding organizer (WO) Berbasis Augmented Reality - Sukmawati Sukmawati; Abdul Zahir; Nur Anisa (Akademi Teknologi Industri Dewantara Palopo, 2025)
This study aims to design an augmented reality-based wedding organizer ( wo) information media as an information and promotional media for Wedding Organizers. The study uses the Research and Development (R&D) method with the ADDIE development approach, which consists of 5 stages: Analyze, Design, Development, Implementation, and Evaluation. System testing is carried out through the Black Box Testing method and validation by media experts. The results of the study indicate that this Augmented Reality application is very valid to use, with a feasibility value of 4.0 from validation by 2 media experts. The customer response also provides very decent results, with an average value of 3.62 from 10 respondents, which measures the real aspects, ease, and advantages that can be categorized as very decent. This application has been implemented and can be accessed via mobile and desktop devices, so it is expected to be an innovative and effective information and promotional media for Wedding Organizer (wo) customers.